Implikatur dan Eksplikatur dalam Konten Youtube Puja Astawa: Kajian Sosiopragmatik - Weddha Savitri, Putu (International Seminar on Austronesian Languages and Literature, 2021)
This article aims to describe the explicature and implicature, as well as the types and functions of the implicatures contained in the short videos of a Balinese content creator named Puja Astawa. This research is a qualitative descriptive study, with data sources in the form of conversations in 5 videos made by Puja Astawa. Data analysis was performed using one of the pragmatic theories, namely the theory of relevance by Sperber regarding the analysis of ‘what is saying’ and ‘implied meanings’. The results of the discussion show that the Puja Astwa video contains implicit meanings that must be understood by the hearer and the types of implicatures that exist are conventional ones. Whereas based on their function, implicatures were found to have assertive, directive, and expressive functions